(untitled) (Comillas Journal of International Relations, 2019)
In this article, it is proposed to formulate the ontological, epistemological and theoretical bases for the constitution of an analytical framework based on the links between the international politics of climate change and the domestic and foreign climate policy of emerging countries. This framework starts from a theoretical triangulation between an ontological perspective of International Relations based on liberalism, an interpretivist epistemological standpoint and constructivist theories on internalization of norms, localization and normative congruence and the concept of global governance. To achieve this objective, it is assumed that the climate policy of emerging countries is strongly conditioned by the degree of overlap between international climate change politics and domestic and foreign climate policy.